Vagotomy by chemoneurolysis: an experimental study in the rat. Issue 2 (February 1983) - Taylor, T V; Holt, S; Andrews, P L; Heading, R C
Abstract : In the pylorus ligated rat vagotomy has been attempted by chemoneurolysis with alcohol. Surgical truncal vagotomy reduced the intragastric acid produced in a five-hour period from 310 +/- 17.6 (SD) mumol to 5.4 +/- 2.4 mumol with a marked reduction in the ulcer score. Injection of 30% alcohol in the region of the vagal trunks at the level of the lower oesophagus produced a marked reduction in gastric acid secretion (7.6 +/- 3.7 mumol). Injection of solutions of alcohol in concentrations over 10% along the lesser curvature reduced gastric acid output to less than 10 mumol with a corresponding reduction in the ulcer score. Four months after the injection of 30% alcohol along the lesser curvature the acid output was 23.0 +/- 5.7 mumol and no gastric ulceration occurred.